Surgical Infections - Evangelos P. Misiakos (Frontiers Research Topics, 2018)
Surgical infections are caused by the breakdown of the equilibrium existing between organisms and the host. This may occur after a breach in a protective surface, as occurs after surgical trauma, changes in host resistance, or particular characteristics of the organism. The possible outcomes are abscess formation, local spread with/without tissue death, distant spread or resolution. A surgical infection is an infection requiring operative treatment (excision or drainage), and occupies an unvascularized space in tissue, or may occur in an operated site. Common examples of the former group are furuncles and carbuncles, hollow viscus inflammations, such as appendicitis, cholecystitis, and most abscesses. The latter group comprises all surgical site infections. This Research Topic provides comprehensive information on the biology, mechanisms, prevention and treatment of surgery-related infections.